The Jekyll and Hyde syndrome : - Engel, Beverly (John Wiley, 2007)
Beverly Engel brings her expertise to this important examination of the Jekyll and Hyde Syndrome—the first book to address this abusive syndrome. She discusses the origins of the disorder, names its seven major manifestations, explains how to identify Jekyll and Hyde behavior in other people and in oneself, and outlines clear steps for how to heal Jekyll and Hyde tendencies for good.